Obtención de semillas de áreas quemadas mediante el procesamiento de imágenes Landsat utilizando los índices NBR Y NDVI (2016)
In this work the way seeds burned areas were obtained in the northern part of South America , using 266 images LANDSAT (5, 7 and 8) in the years 1998, 2003, 2004 , 2007, 2010 , 2013 and 2015 is presented in which he was presented Niño phenomenon . NBR and NDVI indices were used at two points for each scene (pre and post fire) processing images in ESRI ArcGIS software , the Image Analysis tool. Was obtained as a result of the year with more area burned in the study area was 1998, followed by 2003 and the area more fires occurred in the period of time analyzed was that of the Path scene 5 - Row: 55, followed by the Path scene : 4 - Row: 55, which cover the southwest of Venezuela corresponding to the rock formations of the Cinaruco Galeras , in the region of the state of Apure .